How Does Indian Monsoon Regulate the Northern Hemisphere Stationary Wave Pattern? - Son, Jun-Hyeok; Seo, Kyong-Hwan; Son, Seok-Woo; Cha, Dong-Hyun (Frontiers in Earth Science, 2021)
The northern hemisphere summer climate is strongly affected by a circum-global stationary Rossby wave train, which can be manifested by the first EOF mode of the geopotential height at 200 hPa. Interannual variation of this Northern Hemisphere wave (NHW) pattern has a significant impact on remarkably warm surface temperature anomalies over the North Atlantic, Northeast Europe, East Asia to Central-North Pacific, and America, particularly in 2018 and 2010. The NHW pattern is likely generated by atmospheric diabatic heating and vorticity forcing: diabatic heating is mainly confined in the Indian summer monsoon (ISM) precipitation region, whereas the anti-cyclonic vorticity forcing is distributed in the globe. The ISM is a well-known diabatic heat source; however, the main source of vorticity forcing has not been established. In general, the tropical vorticity anomaly comes from diabatic heating-induced atmospheric waves and randomly generated inherent internal waves. The Linear Baroclinic Model experiment reveals that the NHW pattern can be generated by the westward propagating tropical waves generated by the ISM diabatic heat forcing.